2022
DOI: 10.1038/s41550-022-01745-5
|View full text |Cite
|
Sign up to set email alerts
|

A pristine record of outer Solar System materials from asteroid Ryugu’s returned sample

Abstract: Volatile and organic-rich C-type asteroids may have been one of the main sources of Earth’s water. Our best insight into their chemistry is currently provided by carbonaceous chondritic meteorites, but the meteorite record is biased: only the strongest types survive atmospheric entry and are then modified by interaction with the terrestrial environment. Here we present the results of a detailed bulk and microanalytical study of pristine Ryugu particles, brought to Earth by the Hayabusa2 spacecraft. Ryugu parti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
39
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 49 publications
10
39
1
1
Order By: Relevance
“…The exceptionally low abundance of npFe 0 in Ryugu grains is in stark contrast to lunar and Itokawa surface samples, which contain abundant npFe 0 in both radiation-damaged layers on ferromagnesian consistent with other recent studies [27][28][29][30][31] . Therefore, to understand the space weathering of Ryugu grains is to understand the weathering of the most chemically primitive Solar System material.…”
Section: Exceptionally Rare Npfe 0 On Ryugusupporting
confidence: 88%
“…The exceptionally low abundance of npFe 0 in Ryugu grains is in stark contrast to lunar and Itokawa surface samples, which contain abundant npFe 0 in both radiation-damaged layers on ferromagnesian consistent with other recent studies [27][28][29][30][31] . Therefore, to understand the space weathering of Ryugu grains is to understand the weathering of the most chemically primitive Solar System material.…”
Section: Exceptionally Rare Npfe 0 On Ryugusupporting
confidence: 88%
“…More importantly, the unfractionated chemical compositions and volatile element-rich nature of CI chondrites and Ryugu support the view that they formed beyond the snow line, mostly from material that experienced minimal thermal processing. The heavy hydrogen and nitrogen isotopic compositions of Ryugu are also consistent with an outer Solar System origin (34). The findings that CI chondrites and Ryugu share the same nucleosynthetic heritage (Fig.…”
Section: Discussionsupporting
confidence: 72%
“…The findings that CI chondrites and Ryugu share the same nucleosynthetic heritage (Fig. 3) and have close mineralogical, chemical, and isotopic characteristics ( 6 , 34 ), therefore, suggest that these objects formed contemporaneously and were co-located in the same outer Solar System reservoir. It is even possible, although not required by the data, that CI chondrites and the NEO Ryugu originally derived from the same precursor object, which was fragmented by collision during its residence in the inner Main Belt ( 4 , 35 ).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In astronomy, in the asteroid Ryugu’s returned sample, it was found that an aliphatic carbon-rich organic matter was concentrated in coarse-grained hydrous silicate minerals. This means that the coarse-grained hydrous silicate minerals as a shell wall became cradles of organic matter and water and were transported to earth intact 15 . For energy application, phase change materials have been enclosed in various shell walls for thermal energy storage 16 – 20 .…”
Section: Introductionmentioning
confidence: 99%